Yozgatlı Ihsan Efendi: Kaybolan Dünyadan Nurlu Bir Sima by Ekmeleddin İhsanoğlu (American Journal of Islam and Society, 2020)
The growing field of the intellectual and social history of the interwar period is richer for this biography of Yozgatlı Ihsan Efendi, written by his son, Professor Ekmeleddin İhsanoğlu, and titled Yozgatlı Ihsan Efendi: Kaybolan Dünyadan Nurlu Bir Sima (Yozgatlı Ihsan Efendi: An Illuminated Face from a Lost World). The title of the book lends itself to layered interpretation: the word sîmâ (face, but also sign) indicates that it is about a historical persona, Yozgatlı Ihsan Efendi: Islamic scholar, dedicated teacher and a member of the late Ottoman ulama, as well as a witness to the dramatic changes of the early 20th century. On the other hand, Yozgatlı Ihsan Efendi appears as deeply human, in roles that are not readily visible in other historical sources: devoted son, caring father to his own family, and a mentor to many students who passed through Cairo.Download